THE CONCEPT OF MULTI-LEVEL MARKETING FOR INNOVATIVE STARTUP - B. Tokarev (Вестник университета)
The article deals with the problem of develop and lead out an innovative product to the market. Every innovative startup passes by development a set of stages, from research of new technology to market growth and assortment expansion. All stages of development contain inherent marketing actions, which are based on the results of marketing research. Goals and objectives of these studies are very strongly correlated with the content of each stage. The article is discuss a problem of understanding the marketing place and essence for innovation product startup. The model for marketing startup formed for supporting innovative product from concept to market development. It is shown appointment events linked with estimates of future product development for each stage. It is shown that consumers are differ from one stage life stile to another. In general, the findings contribute to the choice of methods of marketing to implement market opportunities for innovative product.